Grand Challenges of Planetary Governance Global Order in Turbulent Times - Young, Oran R. (Edward Elgar Publishing, 2021)
In this timely book, leading scholar Oran Young reflects on the future of the global order. Developing new lenses through which to consider needs for governance arising on a global scale, Young investigates the grand challenges of the 21st century requiring the most urgent and sustained planetary responses: protecting the Earth's climate system; controlling the eruption of pandemics; suppressing disruptive uses of cyberspace; and guiding the biotechnology revolution.